Axion helioscopes as solar thermometers - Hoof, Sebastian; Jaeckel, Joerg; Thormaehlen, Lennert J. (Journal of cosmology and astroparticle physics, 2023)
Axions, if discovered, could serve as a powerful new messenger for studying astrophysical objects. In this study we show how the Sun's spatial and spectral “axion image” can be inverted to infer the radial dependence of solar properties in a model-independent way. In particular, the future helioscope IAXO may allow us to accurately reconstruct the Sun's temperature profile T(r) in the region up to about 80% (40%) of the solar radius for an axion-photon coupling g aγγ of 6 × 10-11 GeV-1 (10-11 GeV-1). The statistical fluctuations in the photon data lead to a median precision of better than 10% (16%) in this region, and the corresponding median accuracy was better than 4% (7%). While our approach can simultaneously infer the radial profile of the Debye scale κ s(r), its weaker connection to the axion production rate leads to median accuracy and precision of worse than 30% and 50%, respectively. We discuss possible challenges and improvements for realistic setups, as well as extensions to more general axion models. We also highlight advantages of helioscopes over neutrino detectors.
Published October 6, 2023
Gesehen am 06.08.2024